LA CREATIVIDAD PEDAGÓGICA-DIDÁCTICA PARA EL PROCESO ENSEÑANZA-APRENDIZAJE DEL IDIOMA DE INGLES DEL DEPARTAMENTO DE IDIOMAS EXTRANJERO DE LA UNIVERSIDAD TÉCNICA DE BABAHOYO. - CHICO VERA MERCY TEOLINDA (2015)
THE PEDAGOGICAL-DIDACTIC CREATIVITY FOR THE TEACHING-LEARNING PROCESS OF THE ENGLISH LANGUAGE OF THE DEPARTMENT OF FOREIGN LANGUAGES OF THE TECHNICAL UNIVERSITY OF BABAHOYO.